2018
DOI: 10.1155/2018/2098908
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Seroprevalence and Risk Factors ofNeospora caninumInfection in Tibetan Sheep in China

Abstract: Neospora caninum is an intracellular protozoan parasite which can cause abortion and stillbirth in ruminants. However, there is no information on Tibetan sheep N. caninum infection in China. A total of 2187 serum samples were collected from Tibetan sheep in the major production areas of Luqu, Maqu, and Tianzhu in Gansu province, and Nyingchi in southeast Tibet, China. All samples were analyzed for the presence of antibodies to N. caninum using a competitive-inhibition enzyme-linked immunoassay. Of the 2187 ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
(17 reference statements)
0
10
2
Order By: Relevance
“…The seroprevalence of N. caninum in male was significantly higher than in female in Tibetan Sheep from China (Nie et al, 2018), which is contrary to data reported by Rizzo et al, 2018 who found a higher prevalence in female sheep from São Paulo state; however, but we did not find such an association in the present study (Table 2). Other authors also did not find an association with sex (Faria et al, 2010;Salaberry et al, 2010).…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…The seroprevalence of N. caninum in male was significantly higher than in female in Tibetan Sheep from China (Nie et al, 2018), which is contrary to data reported by Rizzo et al, 2018 who found a higher prevalence in female sheep from São Paulo state; however, but we did not find such an association in the present study (Table 2). Other authors also did not find an association with sex (Faria et al, 2010;Salaberry et al, 2010).…”
contrasting
confidence: 99%
“…Compared with other countries in the world, the lowest prevalence was in New Zealand (0.6%), Argentina (1.54%), China (8.4) and Costa Rica (10.9%) (Hecker et al, 2018;Nie et al, 2018;Reichel, Ross, & McAllister, 2008;Villagra-Blanco et al, 2019). Accordingly, Cerqueira-Cézar et al (2017) more serological studies for N. caninum infection in animals have been conducted in Brazil than the rest of the world, however, these results are not comparable due to differences in serological tests, cut-offs, and antigens used.…”
mentioning
confidence: 96%
“…The differences in the infection rates in the present study may be related to effects of some environmental conditions (humidity and temperatures), which are considered an important factor for increase resistant of oocysts in the soil or may be due to the increase the spread of insects, that play an important role as mechanical transmitter vectors for oocysts. Also, it was found that the infection influence by the differences between day and night temperature (39). Conclusion In conclusion: Our study recorded for the first time antibodies against Neospora caninum in local breed chickens at Al-Fallujah district, with a moderate infection rate that significantly affected by sex, months, and areas.…”
Section: Infection Rate According To Months: -mentioning
confidence: 52%
“…In Italy, Gazzonis et al (2016) found an occurrence of 19.3%, and demonstrated the well-known variables that affect the presence of N. caninum in sheep herds, such as the rearing system and farm size; small and family-run farms were at a higher risk, and outcomes from the survey mainly indicated that these farms should implement proper sanitary measures and monitor the spread of the infection among small ruminants. In China, Nie et al (2018) found a seroprevalence of 8.4%, and observed that the seroprevalence of N. caninum in male Tibetan sheep (10.8%) was significantly higher than in females (7.4%; p<0.01); this is probably related to the different hormone levels between males and females. According to Azevedo Filho et al (2017), vertical transmission (11%) was clearly detected in a sheep flock.…”
Section: /6mentioning
confidence: 95%